PENGARUH PAKAN KOMERSIAL YANG DIPERKAYA TEPUNG WORTEL (Daucus carota) SEBAGAI SUMBER KAROTEN TERHADAP PENINGKATAN KUALITAS WARNA IKAN GUPPY (Poecilia reticulata) - Sri Marnani; Ren Fitriadi; Arinta Putri (Jurnal Akuakultur Rawa Indonesia, 2022)
Guppy fish is one of the ornamental fish commodities that is quite in demand, because of its various types with beautiful colors. The purpose of this study was to determine the effect of adding carrot flour in commercial feed to improve the color quality of guppy fish and the best dose. The test fish used were male guppy fish strain HB red with sizes ranging from 2–3 cm. This research was conducted using an experimental design, namely a Completely Randomized Design (CRD) consisting of five treatments (commercial feed enriched with carrot flour as much as 0%; 2,5%; 5%; 7,5%; 10%) and three replications. The results showed that the addition of a dose of carrot flour had an effect on improving the color quality of guppies and the highest color quality improvement was found in treatment 4 (10% 2 carrot flour) with a chroma value of 3.97±0,18c , while in the control treatment, treatment 1, treatment 2, and treatment 3 got chroma values of 1.26±0.12a, 1.28±0.03a, 1.71±0.06a, 2.72±0.31b. Survival showed the results were not significantly different, that is 100%. Water quality includes an average temperature of 25,5– 26,6?C, pH 7–8, DO 6,7–7,8 mg/L. Key words : HB Red; Carotene; Chroma value; Survival